2014
DOI: 10.1097/ta.0000000000000155
|View full text |Cite
|
Sign up to set email alerts
|

Management of children with mild traumatic brain injury and intracranial hemorrhage

Abstract: BACKGROUND Traumatic brain injury (TBI) is a significant public health problem affecting tens of thousands of children each year, and an important subset of these patients sustains intracranial hemorrhage (ICH). The purpose of this study was to test the hypothesis that we could identify a subset of children with traumatic ICH who could be monitored on a general neurosurgery ward with a low risk of clinical deterioration. METHODS We performed a retrospective review of pediatric patients ≤18 years of age with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 26 publications
(40 reference statements)
3
42
1
2
Order By: Relevance
“…Only 4 of 113 children required emergency surgery or more intensive care, which is similar to published data for mild head trauma. 15 Only 2.6% of our patients received secondary surgical management compared with a higher rate of secondary surgical management reported by authors of other studies, ranging from 10 14 to 13.1% 13 in children with ICLs, but the initial severity of the head trauma was not specified.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…Only 4 of 113 children required emergency surgery or more intensive care, which is similar to published data for mild head trauma. 15 Only 2.6% of our patients received secondary surgical management compared with a higher rate of secondary surgical management reported by authors of other studies, ranging from 10 14 to 13.1% 13 in children with ICLs, but the initial severity of the head trauma was not specified.…”
Section: Discussioncontrasting
confidence: 53%
“…There are no recommendations on the management and clinical or iconographic monitoring for delineation of risk factors for clinical deterioration in children with intracranial lesions following minor or moderate head trauma. [10][11][12][13][14][15] We wanted to study the management of these children with non-critical intracranial lesions to optimize the approach adopted. The children were hospitalized in the neuropediatric and neurosurgery departments of Toulouse University Hospital.…”
Section: Introductionmentioning
confidence: 99%
“…Our data answers a specific question that previous papers have alluded to, but not emphasized, in their results [6, 7, 10, 12, 14, 15]. To briefly summarize, Arrey et al [6] determined that there was no need to hospitalize 326 patients with ILSF with a median age of 19 months unless there was a pending nonaccidental trauma workup.…”
Section: Discussionmentioning
confidence: 58%
“…Addioui et al [14] showed that of 180 patients, only 4.4% required intervention for dural repair or elevation of depressed fractures despite 32% having subdural, epidural, or subarachnoid hemorrhage, or intracranial contusions. Greenberg et al [15] found that the presence of epidural hemorrhage, intraventricular hemorrhage, coagulopathy, or significant comorbid neurosurgical lesion confers a higher risk for clinically important neurologic decline and need for neurosurgical intervention. Interestingly, Tavor et al [17] retrospectively demonstrated that severe mechanism of injury (running, biking, fall onto protruding instrument) combined with clinically evident skull fracture, neurological deficit, and severe headache identified almost all 182 patients who required intervention in their study.…”
Section: Discussionmentioning
confidence: 99%
“…По данным литературы, в 1,5-8 % случаев у детей с клиническими критериями ЛЧМТ вы-являют следующие значимые травматические структурные внутричерепные изменения (СВИ): эпидуральные гематомы (16 %), субдуральные гематомы (37 %), паренхиматозные кровоизлия-ния (44 %), субарахноидальные кровоизлияния (24 %) и внутрижелудочковые кровоизлияния (4 %) [2,3]. Транзиторный характер общемозго-вой и очаговой неврологической симптоматики в детском возрасте уменьшает значимость кли-нической оценки при выявлении ослож ненного течения ЛЧМТ и требует использования методов нейровизуализации для уточнения тяжести ЧМТ [4,5].…”
Section: актуальностьunclassified